Does Α-synuclein level in biological fluids correlate with severity of cognitive impairment in patients with Parkinson’s disease? (Review) - Demchenko, A. V.; Biriuk V. V.; Демченко, Аліна Вікторівна; Бірюк, В. В. (Czech Republic: European Scientific Center Biologial Marker, 2019)
There are many investigations about the role of α-synuclein as a possible biomarker of Parkinson’s disease (PD). The majority of researches consists data about the level of α-synuclein and its oligomers in patients with different stages of PD. One of the latest metaanalysis of 10 publications about α-synuclein level in total 1302 participants, performed by Bougea A. et al. [4], showed that total plasma α-synuclein levels were higher in PD patients than controls.
Keywords: α-synuclein; Parkinson’s; cognitive; cognitive evoked potentials; plasma